After Iraq: U.S.-UN Relations - Brown, Mark Malloch (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer The UNDP Administrator speaks at The Fletcher School, sharing an optimistic outlook on the Iraq War and the future of U.S.-UN relations.